Effects of foreign direct investment on economic growth in Colombia: empirical evidence 2000-2010 - Moyano Buitrago, María Luz; Gil León, José Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this article the effect of FDI on economic growth in Colombia is analyzed, and shown that these flows caused effects, both direct and indirect, in the national economy between 2000-2010. Thus, the econometric exercise was possible to deduce that affect FDI flows and moderately positive growth of the Colombian economy, and this led to the conclusion that given the conditions of the national economy and the global economic climate in this period, FDI contributed to percentage increase in GDP, in the same way, to deepen the aggregate and sectoral economic times it brings.